Influence of pre-treatment on some physical-chemical properties of dried carrots - Guiné, Raquel (2014)
Introduction: Carrot is the most commonly used vegetable for human nutrition and is an excellent source of β-carotene, vitamin A and potassium, and contains cholesterol-lowering pectin, vitamin C, vitamin B6, thiamine, folic acid, and magnesium. Carrots are highly seasonal and abundantly available at particular times of the year. For extending the availability of this root, several preservation processes can be used, but convective drying is one of the most important since it not only extends vegetable shelf life significantly but also diversifies the offer of foods for consumers. However, convective drying can also give rise to significant chemical changes (non-enzymatic browning, among others), which may affect the quality of the product. Pre-drying treatments of solid food products can be used as a way to augment product quality and to modify the structure of food products so as to improve mass transfer coefficients in drying. In this context, assessments of the physical and chemical properties were made in order to investigate the effects of sodium metabisulphite at different concentration/time combinations prior convective drying of carrots. Materials and methods: The carrots used in this study were purchased in a local market, and hand peeled and cut into slices with thickness of 10 mm. Before convective drying at 60ºC the slices of carrots were submitted to pre-treatments as follows: a) dipping in a water solution of 0.25% of sodium metabisulphite for 60 and 90 min. and 1% of sodium metabisulphite for the same times, at room temperature; b) dipping in an equal mass of plain water for 60 and 90 min at room temperature (as control sample) . Some chemical properties of the fresh and dried samples were evaluated, namely moisture content, fibre, ashes and sugars (reducing, total and non-reducing sugars). The physical properties evaluated were color and texture. Results: The main results show that the different combinations concentration/time of sodium metbishulphite dipping have a similar effect on the chemical properties of the dried carrots. Furthermore, the dried slices of carrots with and without pre-treatment originated products with similar nutritional characteristics. With respect of colour, the total difference of colour and browning index was similar to the different solutions of sodium metabishulphite. In addition the browning of the dried carrots was, apparently, independent of the pre-treatment. Similarly, the different combinations of pre-treatment had no visible effect on textural parameters and generally the hardness decreased with the pre-treatments. Conclusions: From the obtained results it was concluded that the different concentration/time combinations of sodium metabisulphite solutions had no visible improvement on the quality of the dried carrots.